MODELING AND OPTIMIZATION OF DUAL STRING GAS LIFT SPLIT FACTOR IN OIL PRODUCERS - LAW , CHEW CHEN (2020)
Dual String completion has been around since the 50’s. It remained as one of the most common completion and production strategies due to its cost advantage. However, gas lifting for this type of completion can be complicated. This is due to the operating condition where total gas is injected into the common annulus and then allowed to be distributed among the two strings: long string (LS) and short string (SS), without any surface control. High uncertainties often result from the methods used to determine the split factor—the ratio between the gas lift rates to one string over the total gas injected. “Current” methods rely on modelling the strings as individual wells, without accounting for the flow path of the gas in the annulus.